Experimental studies on compaction of soil with HAMM 3411 vibrating roller - I. S. Tyuremnov; A. S. Krayushkin; D. A. Shorokhov (Вестник СибАДИ, 2023)
Introduction. Mathematical modelling is used to assess the influence of various factors on the result of soil compaction by a vibratory roller. The verification of the mathematical model is carried out by comparing it with the results of the experimental studies. Expanding the list of the roller models in the experimental studies allows expanding the range of conditions for verification of the mathematical model. The article presents the results of field experimental studies of soil compaction by HAMM 3411 vibrating roller. The data on the change in the value of the dynamic soil deformation modulus Evd depending on the number of passes of the roller during compaction of sandgravel mixture with a layer thickness of 0.5 m have been obtained. The peculiarities that are reasonable to take into account when carrying out further experimental research are revealed.Materials and methods. The experimental studies of the scope of vertical movements of the roller, as well as vertical accelerations of the roller and its frame were carried out on a HAMM 3411 vibrating roller during compaction of a sand-gravel mixture. The result of compaction of the soil after each pass was estimated by the value of the dynamic deformation modulus Evd, measured using the ZORN ZFG 3.0 dynamic loading unit. In the experiment, vertical movements of the vibrating roller were recorded using a BAUMER OADM 13U6480/S35A laser sensor. Accelerations of vibrations of the vibrating roller and the roller frame were recorded by piezoelectric accelerometers of the AR2099-100 and AR99-100 models. When processing sensor readings, digital signal processing technology was used – low-pass filters with a limit frequency of 200 Hz.Results. The studies were carried out on two sites with different soil moisture. On a site with waterlogged soil in the range of Evd values = 10 ...13 MPa, the amplitude values of the vertical accelerations of the roller were in the range from +20 ... +45 to -25 ...-43 m/s2, and the frames in the range from +2.5 ...+5 to -2 ...-5 m/s2. The range of vibrations of the vibrating roller in the area with waterlogged soil was 3.3...4.8 mm. On a site with soil with close to optimal importance, in the range of values Evd= 18...28 MPa, the amplitude values of vertical accelerations of the roller were in the range from +36 ... +48 to -35 ... -40 m/s2, and frames in the range from +3.5 ... +6 to -2...-4.5 m/s2.Discussion and conclusion. The results show that the range of oscillations of the drum, as well as the amplitude values of vertical accelerations of the drum and the drum frame slightly increase with increasing soil deformation modulus Evd. The results of the experiment correlate with the studies conducted on the models of rollers DM-DM-617. When measuring values of Evd in one cross-section, the difference between measured values along the axis of roller’s movement and on the pneumatic wheel track reached 30%. When analyzing obtained results, it is necessary to take into account that in the experiment the actual frequency of oscillation of the roller was 18 Hz, instead of 27 Hz as stated in the technical specifications. With such reduction of frequency, the forced force of oscillations will decrease approximately 2.25 times.  Results of the experiment will help in further verification of mathematical model of the roller and in carrying out experimental researches of similar character.